2014
DOI: 10.1111/1365-2745.12247
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition explains soil respiration responses to changing carbon inputs along anAndes‐to‐Amazon elevation gradient

Abstract: 1. The Andes are predicted to warm by 3–5 °C this century with the potential to alter the processes regulating carbon (C) cycling in these tropical forest soils. This rapid warming is expected to stimulate soil microbial respiration and change plant species distributions, thereby affecting the quantity and quality of C inputs to the soil and influencing the quantity of soil-derived CO2 released to the atmosphere.2. We studied tropical lowland, premontane and montane forest soils taken from along a 3200-m eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 95 publications
(209 reference statements)
11
101
2
5
Order By: Relevance
“…2b and 3b-d). This result supported our second hypothesis and, when examined alongside evidence for fungal dominance of the microbial community at higher elevation (Traunspurger et al 2017;Whitaker et al 2014), provided a degree of indirect support for our first hypothesis of a more N-constrained fungal-dominated community at higher elevation. This hypothesis was also indirectly supported by a previous study of enzymatic stoichiometry in the same sites, which showed an increase in the ratio of N-to Pdegrading soil enzyme activities with increased elevation (Nottingham et al 2015b).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…2b and 3b-d). This result supported our second hypothesis and, when examined alongside evidence for fungal dominance of the microbial community at higher elevation (Traunspurger et al 2017;Whitaker et al 2014), provided a degree of indirect support for our first hypothesis of a more N-constrained fungal-dominated community at higher elevation. This hypothesis was also indirectly supported by a previous study of enzymatic stoichiometry in the same sites, which showed an increase in the ratio of N-to Pdegrading soil enzyme activities with increased elevation (Nottingham et al 2015b).…”
Section: Discussionsupporting
confidence: 83%
“…Further descriptions of soil properties (Quesada et al 2010;Whitaker et al 2014;Zimmermann et al 2009), climate (Rapp and Silman 2012) and aboveground productivity and floristic composition (Asner et al 2013;Feeley et al 2011;Girardin et al 2010) for these sites are reported elsewhere.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found negative correlation between soil microbial biomass and elevation in the study region, which was not in line with some previous studies that reported a positive relationship between soil microbial biomass and elevation below 3000 m in elevation (Huang et al, 2014;Pabst et al, 2013;Wardle, 1992;Whitaker et al, 2014). Our result was supported by the recent finding that soil microbial biomass phosphorus decreases with elevation above 3500 m on the eastern slope of Gongga Mountain, China (Sun et al, 2013a) and was helpful in refining the current understanding of soil microbial biomass distributions.…”
Section: Relationships Between Soil Microbial Biomass and Elevation Icontrasting
confidence: 55%
“…It is not yet clear how emergent microbial properties and responses vary with state factor gradients. There have been some studies of microbial trait parameters across environmental gradients [German et al, 2012;Whitaker et al, 2014], but more studies with additional environmental drivers are needed to scale up to the global level. Additional gridded data products on state factor variables at the global scale represent another key need for scaling up these models.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%